PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN VIDEO ANIMASI TERHADAP HASIL BELAJAR BAHASA INDONESIA KELAS II SDN BANYUANYAR 1 SURAKARTA - Mulyati, M (PERMAI: Jurnal Pendidikan dan Literasi Madrasah Ibtida'iyah, 2023)
This research is an experimental research with a one group pretest-posttest design with a quantitative approach. The data analysis technique used is descriptive statistics. The purpose of this study was to determine the effect of using animated video learning media on Indonesian language learning outcomes in Class II at SDN Banyuanyar 1 Surakarta, Central Java. Based on the results of the research conducted, there are results, namely the initial knowledge of 27 students before being given treatment using animated video learning media shows an average value of 65.97 (mean pretest) and student knowledge after being given treatment using animated video learning media shows an increase in average value -the average achieved was 76.84 (mean posttest). The difference between the mean pretest and mean posttest is 10.87. This shows that there is an effect of the use of animated video media on the learning outcomes of Indonesian in Class II SDN Banyuanyar 1 Surakarta.Keywords: Animation video media, learning outcomes, Primary School